Health Improvement and Educational Attainment in Secondary Schools: Complementary or Competing Priorities? Exploratory Analyses From the School Health Research Network in Wales. (August 2018) - Littlecott, Hannah J.; Long, Sara; Hawkins, Jemma; Murphy, Simon; Hewitt, Gillian; Eccles, Gemma; Fletcher, Adam; Moore, Graham F.
Background . Implementing health improvement is often perceived as diverting resource away from schools' core business, reflecting an assumption of a "zero-sum game" between health and education. There is some evidence that health behaviors may affect young people's educational outcomes. However, associations between implementation of school health improvement and educational outcomes remains underinvestigated. Methods . The study linked school-level data on free school meal (FSM) entitlement, educational outcomes, and school attendance, obtained from government websites, with data from the School Environment Questionnaire (SEQ) on health improvement activity collected in Wales (2015/2016). Spearman's rank correlation coefficients and linear regression models tested the extent of association between health improvement activity and attendance and educational outcomes. Results . SEQ data were provided by 100/115 network schools (87%), of whom data on educational performance were obtained from 97. The percentage of pupils entitled to FSM predicted most of the between-school variance in achievement and attendance. Linear regression models demonstrated significant positive associations of all measures of health improvement activity with attainment at Key Stage (KS) 3, apart from mental health education in the curriculum and organizational commitment to health. Student and parent involvement in planning health activities were associated with improved school attendance. There were no significant associations between health improvement and KS4 attainment. Conclusion . Implementing health improvement activity does not have a detrimental effect on schools' educational performance. There is tentative evidence of the reverse, with better educational outcomes in schools with more extensive health improvement policies and practices. Further research should investigate processes by which this occurs and variations by socioeconomic status.